2015
DOI: 10.1002/ajmg.a.37047
|View full text |Cite
|
Sign up to set email alerts
|

MED23‐associated intellectual disability in a non‐consanguineous family

Abstract: Intellectual disability (ID) is a heterogeneous condition arising from a variety of environmental and genetic factors. Among these causes are defects in transcriptional regulators. Herein, we report two brothers in a non-consanguineous family with novel compound heterozygous, disease-segregating mutations (NM_015979.3: [3656A>G];[4006C>T], NP_057063.2: [H1219R];[R1336X]) in MED23. This gene encodes a subunit of the Mediator complex that modulates the expression of RNA polymerase II-dependent genes. These broth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 15 publications
3
28
0
Order By: Relevance
“…So far, only four variants in the MED23 have been associated with an autosomal recessive form of ID and refractory epilepsy . The summary of MED23 variants is summarized in Table .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…So far, only four variants in the MED23 have been associated with an autosomal recessive form of ID and refractory epilepsy . The summary of MED23 variants is summarized in Table .…”
Section: Discussionmentioning
confidence: 99%
“…They found that the p.R617Q variant did not affect MED23 expression levels, protein stability, architecture, or composition of the whole Mediator complex, but specifically impaired the response of the JUN and the FOS , immediate‐early genes to serum mitogens . The same gene was mutated in two brothers in a nonconsanguineous family with novel compound heterozygous mutations, 3656A>G and 4006C>T, in MED23 . The patients had severe ID, spasticity, congenital heart diseases, brain abnormalities, and atypical electroencephalography.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations